Analisis Restorasi Pasca Perawatan Pulpektomi Gigi Decidui pada Anak: Tinjauan Literatur tentang Metode dan Efektivitasnya - Selvia Maysaroh; Lasmi Dewi Nuraini (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Half of the 75 million children in Indonesia suffer from dental caries, and the number continues to rise each year. Caries is a disease that involves the enamel, dentin, and pulp of the tooth. If left untreated, it can reach the pulp and cause tooth necrosis. Pulpectomy is a dental procedure that involves removing the entire pulp tissue of deciduous teeth to access the infected root canal. This procedure is crucial to prevent the spread of infection. Post-pulpectomy restoration is essential to ensure the optimal function of the tooth and prevent further damage to the remaining tooth structure. The restoration must have adequate retention, minimal leakage, and not increase the risk of further damage to the remaining tooth structure. Methodology: This study is a qualitative research in the form of a literature review using secondary data collected in August 2024 from five main databases: PubMed, MDPI, ScienceDirect, Garuda (Garba Rujukan Digital), and Taylor & Francis. The collected data were then sorted to identify articles relevant to the research criteria. Results and Discussion: Based on the Prisma Diagram Flow, 343 articles were identified from the five databases, which were then filtered down to five articles that met the criteria to be the primary articles in this literature review. The results show that there are various types of post-pulpectomy restorations tailored to the diagnosis and clinical indications of the treated teeth. Conclusion: There are two commonly used types of post-pulpectomy restorations, namely restorations made of Glass Ionomer Cement (GIC) and Stainless Steel Crowns (SSC). Both of these restorations can be modified into space maintainers, which are essential in preserving space for the future growth of permanent teeth while improving the function of the treated tooth.